2013
DOI: 10.1016/j.agee.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Detecting pest control services across spatial and temporal scales

Abstract: a b s t r a c tNatural habitat may deliver ecosystem services to agriculture through the provision of natural enemies of agricultural pests. Natural or non-crop habitat has strongly positive effects on natural enemies in cropland, but the resulting impact on pests is not as well established. This study measured weekly natural enemy (syrphid fly larvae) and pest (cabbage aphid) abundances in Central California broccoli fields for three years. Abundance of syrphid fly larvae increased strongly with the proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 52 publications
3
72
0
4
Order By: Relevance
“…Moreover, many studies, experimental or empirical, have shown that pollination of crops by bees depend on the landscape features, with greater pollination in landscapes with a higher density of semi-natural elements (Carvalheiro et al 2010;Le Féon et al 2013;Kennedy et al 2013) although the effect also depends on the spatial scale (Steffan-Dewenter and Westphal 2008). Similarly, the pollination services provided to crops were shown to decrease with isolation from natural elements in the landscape, reducing both crop yields and their stability over time (Garibaldi et al 2011;Chaplin-Kramer et al 2013). In return, mass-flowering crops provide additional food resources and can increase the density of wild pollinators in adjacent habitats (Westphal et al 2003).…”
Section: Are Crops Pollinated By Wild Bees?mentioning
confidence: 99%
“…Moreover, many studies, experimental or empirical, have shown that pollination of crops by bees depend on the landscape features, with greater pollination in landscapes with a higher density of semi-natural elements (Carvalheiro et al 2010;Le Féon et al 2013;Kennedy et al 2013) although the effect also depends on the spatial scale (Steffan-Dewenter and Westphal 2008). Similarly, the pollination services provided to crops were shown to decrease with isolation from natural elements in the landscape, reducing both crop yields and their stability over time (Garibaldi et al 2011;Chaplin-Kramer et al 2013). In return, mass-flowering crops provide additional food resources and can increase the density of wild pollinators in adjacent habitats (Westphal et al 2003).…”
Section: Are Crops Pollinated By Wild Bees?mentioning
confidence: 99%
“…In addition to spatial scales, there is a growing interest in considering the temporal scale in order to identify the relationships between pest densities, natural enemies dynamics and pest control services (Chaplin-Kramer et al, 2013). Past empirical studies generally consider short-term data sets (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors argue that habitat management at a landscape-scale is needed to enhance ecosystem services such as pollination or pest biological control by effective habitat management (Tscharntke et al, 2007). To disentangle the effects of landscape complexity on pests as well as on their natural enemies, it is necessary to identify the appropriate landscape elements, spatial scales and time periods to be considered (Kremen et al, 2007;Chaplin-Kramer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Second, in other cases, the spatial and temporal dynamics of the landscape mosaic may significantly affect pest's population dynamics (Chaplin-Kramer et al, 2013). Most agricultural pests in arable land need to emigrate out of crop fields in autumn and return to crop fields in spring.…”
Section: Technologymentioning
confidence: 99%